2022
DOI: 10.3201/eid2802.211849
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Seroprevalence of Zika and Chikungunya Viruses, Kingston Metropolitan Area, Jamaica, 2017–2019

Abstract: To determine the extent of exposure to Zika virus (ZIKV) and chikungunya virus (CHIKV) in Jamaica, we collected serum from 584 pregnant women during 2017–2019. We found that 15.6% had antibodies against ZIKV and 83.6% against CHIKV. These results indicate potential recirculation of ZIKV but not CHIKV in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
11
2
Order By: Relevance
“…A meta-analysis from the South East and non-South East Asia showed that primary DENV-3 infection and secondary infection with DENV-2, 3 and 4 increased the risk of severe dengue infections ( 34 ). During the 2016 ZIKV epidemic in Jamaica, DENV was co-circulating with ZIKV and was predominantly of the DENV-3 serotype ( 12 , 13 ). Yet, severe disease and case fatality rates in DENV-infected Jamaican children during 2019 were much higher than in 2016, suggesting that secondary DENV infection after a primary ZIKV infection could have impacted disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis from the South East and non-South East Asia showed that primary DENV-3 infection and secondary infection with DENV-2, 3 and 4 increased the risk of severe dengue infections ( 34 ). During the 2016 ZIKV epidemic in Jamaica, DENV was co-circulating with ZIKV and was predominantly of the DENV-3 serotype ( 12 , 13 ). Yet, severe disease and case fatality rates in DENV-infected Jamaican children during 2019 were much higher than in 2016, suggesting that secondary DENV infection after a primary ZIKV infection could have impacted disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…In Jamaica, an upper middle-developing Caribbean islandnation, with population 2.97 million, national surveillance data are available from 1977 for dengue epidemics, where seroprevalence rates approach 99-100% in pregnancy, which is a readily-accessible representative Jamaican subpopulation (8). In 2014, an epidemic with several thousands of suspected cases of chikungunya virus (CHIKV) infections were reported with an 83.6% seropositivity (9)(10)(11)(12). In 2016, Jamaica experienced its maiden Zika virus (ZIKV) epidemic, when all three arboviruses co-circulated endemically (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Freitas, Laura Pezzi, Luciano P.G. Cavalcanti, Fabrice Simon To the Editor: We read with great interest the recent article by Anzinger et al (1), who found a seroprevalence of 83.6% for chikungunya in pregnant women in the metropolitan region of Kingston, Jamaica. These data are similar to the seroprevalence found nationwide by the Jamaica Health and Lifestyle Survey III, 2016-2017 (Ministry of Health and Welfare, Jamaica), which was 82% among women, 78.5% among men, and 80.4% overall.…”
Section: Seroprevalence Of Chikungunya Virus Jamaica and New Tools Fo...mentioning
confidence: 99%
“…National hospital-based surveillance revealed increased annual rates of severe microcephaly from 23.6 per 100,000 live births in 2010 (during the period of DENV outbreaks) to 41.7 per 100,000 live births in 2017 in association with the ZIKV epidemic [ 14 ], alongside surveillance reports of the congenital syndrome associated with ZIKV and related fetal brain disruption sequences temporally and spatially related to reported ZIKV cases [ 14 ]. The congenital syndrome was also being recognized simultaneously in 0.8% to 2.2% of the newborns in 3 urban public maternity hospitals [ 23 ], with a 15.6% ZIKV immunoglobulin G antibody seroprevalence in pregnancy reported [ 19 ]. Other complications included Guillain-Barré syndrome and varied neurological presentations in children and adults [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jamaica has experienced several DENV outbreaks of increasing intensity, severity, and magnitude in recent years (2010, 2012, and 2018-2019), with increased attributable morbidity and mortality in the very young, including reported cases of neonatal microcephaly [11][12][13][14]. Jamaica also experienced an explosive CHIKV epidemic in 2014 [3,[15][16][17][18]: >80% of the general and antenatal populations were affected, with significant perinatal (maternal and newborn) illnesses, increased attributable neonatal morbidity and mortality [3,16,19], and >2500 deaths during the epidemic year nationally [18].…”
Section: Introductionmentioning
confidence: 99%